ANALISIS VIRTUAL GUIDE MONUMENT KAPAL SELAM SURABAYA (MONKASEL) MELALUI PENGGABUNGAN "GOOGLE CARDBOARD" DAN AUGMENTED REALITY - Robithoh Akbar Irzain; Irfansyah Irfansyah; Hilwadi Hindersah (Wimba : Jurnal Komunikasi Visual, 2017)
Submarine monument or known as Monkasel is a submarine museum located in  the center of Surabaya. Submarine Monument which was formerly built as KRI Pasopati 410 submarine, is one of Indonesian Navies. Facilities, technical support and human resources are the main obstacles of the Monkasel tourism  beneficiaries. In addition, the way information communicated is less interesting to the visitors of museum. In order to solve this problem, digital media which utilizes visitor's devices is designed. Digital media enables visitor to access more information interestingly using their device. Therefore, the information provided by artefact and analog information board will be enriched by digital media. The aim of this research is to perceive about digital media appication such as Google Cardboard as virtual reality in collaboration with augmented reality that can be implemented to artefact in Museum Kapal Selam Surabaya. Qualitative explanative and action research are the methods used for this research. By examining the cause and impact of a fenomena, interactive media helps to reconstruct the value of the fenomena. As a result, user's application on mobile gadget is developed with information provided by the museum. By using Google Cardboard as virtual reality device, the user experiences immersive result of the media. Google Carboard is a technology of first person view that has 360 degree angle, while augmented reality is a combination of invisible and visible object in reality. Augmented reality delivers information interestingly to Monkasel Surabaya visitor by using visualisation of two or three dimentional virtual object on a real object.